Deletion of sigma54 (rpoN) alters the rate of autolysis and biofilm formation in Enterococcus faecalis - Hancock, Lynn E.; Iyer, Vijayalakshmi Subramanian (My University, 2012)
Transcription initiation is a critical step in bacterial gene regulation and is often controlled by transcription regulators. The alternate sigma factor (sigma54) is one such regulator that facilitates activator-dependent transcription initiation and thus modulates the expression of a variety of genes involved in metabolism and pathogenesis in bacteria. This study describes the role of sigma54 in the nosocomial pathogen Enterococcus faecalis. Biofilm formation is one of the important pathogenic mechanisms of E. faecalis, as it elevates the organism’s potential to cause surgical site and urinary tract infections. Lysis of bacterial cells within the population contributes to biofilm formation by providing extracellular DNA (eDNA) as a key component of the biofilm matrix. Deletion of rpoN rendered E. faecalis resistant to autolysis, which in turn impaired eDNA release. Despite the significant reduction in eDNA levels compared to the parental strain, the rpoN mutant formed more robust biofilms as observed using laser scanning confocal microscopy and Comstat analysis, indicating and emphasizing the presence of other matrix components. Initial adherence to a polystyrene surface was also enhanced in the mutant. Proteinase K treatment at early stages of biofilm development significantly reduced the accumulation of biofilm by the rpoN mutant. In conclusion, our data indicate that other factors in addition to eDNA might contribute to the overall composition of the enterococcal biofilm and that the regulatory role of sigma54 governs the nature and composition of the biofilm matrix.
Keywords: Enterococcus faecalis; σ54 (rpoN); Biofilm; Extracellular DNA; Autolysis; Sigma54 (rpoN)